2020
DOI: 10.3390/antiox9100950
|View full text |Cite
|
Sign up to set email alerts
|

Key Developments in the Potential of Curcumin for the Treatment of Peripheral Neuropathies

Abstract: Peripheral neuropathies (PN) can be triggered after metabolic diseases, traumatic peripheral nerve injury, genetic mutations, toxic substances, and/or inflammation. PN is a major clinical problem, affecting many patients and with few effective therapeutics. Recently, interest in natural dietary compounds, such as polyphenols, in human health has led to a great deal of research, especially in PN. Curcumin is a polyphenol extracted from the root of Curcuma longa. This molecule has long been used in Asian medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 99 publications
2
18
0
Order By: Relevance
“…A clinical trial revealed that the oral administration with curcumin could significantly improve peripheral neuropathy in patients with type 2 diabetes [34,35] . The study has reported that curcumin at dose ranging from 20 to 300 mg/kg/day was administered (oral or intraperitoneal) for 7 to 140 days [36] . The median lethal dose of curcumin in rats and mice was higher than 2,000 mg/kg BW (oral) [37] .…”
Section: Resultsmentioning
confidence: 99%
“…A clinical trial revealed that the oral administration with curcumin could significantly improve peripheral neuropathy in patients with type 2 diabetes [34,35] . The study has reported that curcumin at dose ranging from 20 to 300 mg/kg/day was administered (oral or intraperitoneal) for 7 to 140 days [36] . The median lethal dose of curcumin in rats and mice was higher than 2,000 mg/kg BW (oral) [37] .…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, painful DPN is mainly manifested as loss of skin sensation and pain in the distal extremities, of which symmetrical pain in the lower extremities is the most common (7). Other manifestations include atypical pain, numbness, acupuncture and burning sensation, and can also be manifested as other neuromotor dysfunctions, such as muscle weakness, poor balance, and tendency to fall (8). Studies have shown that up to 60% of diabetic patients are deeply affected by painful diabetes, leading to the occurrence of serious physical and social diseases, and seriously affecting the quality of life of patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…C. domestica Valeton and C. brog Valeton) ( Zingiberaceae ) used as a culinary spice in curry powder [ 19 ]. The antioxidant and anti-inflammatory properties of curcumin [ 20 , 21 ] could be attributed to its antinociceptive activity against different pain conditions, including peripheral neuropathic, inflammatory, postoperative, burn pain, and wound healing [ 22 , 23 , 24 , 25 ], as well as its use as an oral supplement in the treatment of various inflammatory medical conditions, such as alopecia [ 26 ].…”
Section: Introductionmentioning
confidence: 99%